Analisis Kurikulum Pendidikan dan Pelatihan Jalan Berkeselamatan BPSDM Kementerian PUPR - Najmudin, Dudun; Susanti, Lia; Pebrian, Ilham (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
Road transportation safety is a major challenge in Indonesia, with the number of accidents increasing every year. The Human Resource Development Agency (BPSDM) of the Ministry of Public Works and Public Housing (PUPR) has developed a safe road education and training curriculum as one of the efforts to improve the competence of the workforce in the road transportation sector. This article analyzes the macro and micro curriculum development of the training, including objectives, content, methods, and evaluation. This research uses a descriptive qualitative approach with document analysis. The results of the analysis show that there is a mismatch between the formulation of objectives and the national qualifications framework, a lack of relevance of the material to the needs of society and the latest technology, and deficiencies in assessment methods and instruments. This article recommends revising the curriculum to ensure its relevance and effectiveness in supporting safe driving in Indonesia.